The causal relationship between obesity and skin and soft tissue infections: A two-sample Mendelian randomization study - Hu, Hongxin; Mei, Jian; Lin, Mei; Wu, Xianwei; Lin, Haibin; Chen, Guoli (Frontiers in Endocrinology, 2022)
Objective Many observational studies have shown that obesity strongly affects skin and soft tissue infections (SSTIs). However, whether a causal genetic relationship exists between obesity and SSTIs is unclear. Methods A two-sample Mendelian randomization (MR) study was used to explore whether obesity is causally associated with SSTIs using a publicly released genome-wide association study (GWAS). An inverse-variance weighted (IVW) analysis was used as the primary analysis, and the results are reported as the odds ratios (ORs). Heterogeneity was tested using Cochran’s Q test and the I2 statistic, and horizontal pleiotropy was tested using the MR−Egger intercept and MR pleiotropy residual sum and outlier (MR-PRESSO). Results The results of the MR analysis showed a positive effect of BMI on SSTIs (OR 1.544, 95% CI 1.399-1.704, P= 5.86 × 10-18). After adjusting for the effect of type 2 diabetes (T2D) and peripheral vascular disease (PVD), the positive effect still existed. Then, we further assessed the effect of BMI on different types of SSTIs. The results showed that BMI caused an increased risk of impetigo, cutaneous abscess, furuncle and carbuncle, cellulitis, pilonidal cyst, and other local infections of skin and subcutaneous tissues, except for acute lymphadenitis. However, the associations disappeared after adjusting for the effect of T2D and PVD, and the associations between BMI and impetigo or cellulitis disappeared. Finally, we assessed the effects of several obesity-related characteristics on SSTIs. Waist circumference, hip circumference, body fat percentage, and whole-body fat mass, excluding waist-to-hip ratio, had a causal effect on an increased risk of SSTIs. However, the associations disappeared after adjusting for the effect of BMI. Conclusion This study found that obesity had a positive causal effect on SSTIs. Reasonable weight control is a possible way to reduce the occurrence of SSTIs, especially in patients undergoing surgery.